Princess Mandalika of Lombok: A Gender Equality Hero Defying Power Structures in Folklore - Khirjan Nahdi; Hasan Basri; Amrullah Amrullah; Muhammad Adi Junaidi (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This study aims to reveal a new understanding of Mandalika folklore through Derrida's deconstruction. The goal is to demonstrate that Derrida's approach uncovers objective meanings and offers a theoretical alternative to traditional interpretations. By contextualizing new meanings through deconstruction, the study provides varied insights without relying solely on the author's intended meaning. The research employs Derrida's deconstruction through textual and in-depth analysis, exploring the concept of difference to identify binary contexts in the narrative structure. It includes case studies, comparisons of folkloric versions, interdisciplinary approaches for a comprehensive view, and critical analysis. The process begins with a synopsis representing the entire Mandalika folklore text. Findings indicate that Mandalika folklore’s meanings extend beyond conventional understandings, emerging from dynamic interactions between textual and non-textual elements. These new meanings challenge previous interpretations shaped by authorial authority. The study highlights how Mandalika folklore reflects the patriarchal Sasak society, revealing tragic choices born from social disharmony. It emphasizes the need for the Sasak community to use the Mandalika narrative for reflection and reevaluation of gender relations. The folklore advocates for gender equality, depicting Mandalika as both a hero and a victim of patriarchal norms. This new understanding calls for a reassessment of gender roles and societal expectations.